Neurocognitive decline in cardiac surgery—Distraction rather than destruction?. Issue 1 (20th October 2021) - Caldonazo, Tulio; Kirov, Hristo; Doenst, Torsten
Abstract: Background: A neurocognitive decline is an undesirable event that can be observed in patients after cardiac surgery. It has been related to the use of cardiopulmonary bypass (CPB). Minor embolic or hyperinflammatory mechanisms are thought to be responsible. In this issue of the  Journal of Cardiac Surgery, the neurocognitive decline was observed in 22 of 30 patients after cardiac surgery with CPB. Repeatable neuropsychological status tests were used and scores 4 days after surgery were 5%–15% lower than before. Mechanistic investigations with glycemic control and transcriptomic and cytokine analyses failed to provide an explanation but the frequency of this observation is worrisome. Discussion: However, available evidence suggests that neurocognitive dysfunction disappears within a few months, and later on no difference to controls that did not undergo surgery can be detected. In addition, similar degrees of neurocognitive dysfunction can be observed after noncardiac surgery and even after percutaneous coronary intervention (PCI). A most recent comparison of memory decline after CABG and PCI also suggests no difference between the two invasive treatment options for coronary artery disease. All these findings argue against a primarily CPB‐associated mechanism. Interestingly, test subjects from a consumer investigation showed a 10% decline in their working memory just by placing their cell phone on the table, suggesting that being distracted may also affect neurocognitive function. Given the reversibility of surgery‐ and intervention‐associated neurocognitive dysfunction, we question destructive, embolic, or inflammatory‐associated mechanisms. Distractive aspects of intervention‐associated stress may also play a role. Conclusion: In any case, neurocognitive decline after cardiac surgery does not appear to be surgery‐specific.